Identifikasi Varietas Pisang di Kecamatan Jambi Luar Kota - Jovita Zahra (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
This study on the Identification of Banana Varieties in the Jambi Luar Kota District aims to classify four types of bananas found-Ambon Banana, Lemak Manis Banana, Kepok Banana, and Sarawak Banana-based on morphological characters and genetic relationships using MEGA 12 software. The results of the phylogenetic analysis divided these varieties into two main groups originating from the genus Musa.The nucleotide sequences of the target gene from several banana cultivars were downloaded from the NCBI GenBank database using the following accession numbers: MT227509.1 (Musa acuminata Ambon matk), MZ318122.1 (Musa acuminata Pisang Lilin matk), FJ871652.1 (Musa paradisiaca Kepok matk), and MZ318108.1 (Musa acuminata Serawak matk). The robustness of the generated phylogenetic tree was evaluated through 1,000 bootstrap replications to assess the confidence level of each branch. The final tree topology was then interpreted to determine the genetic relationships among the analyzed banana cultivars.